2021
DOI: 10.3390/vaccines9111329
|View full text |Cite
|
Sign up to set email alerts
|

Public Interest in Distribution and Determinants of Influenza and Pneumonia Vaccination during the COVID-19 Pandemic: An Infodemiology and Cross-Sectional Study from China

Abstract: Background: Following the COVID-19 pandemic, global interest in influenza vaccines and pneumonia vaccines has increased significantly. We aimed to examine public interest in and actual market circulation of influenza and pneumonia vaccines before and after the initial outbreak of COVID-19 and estimate the coverage and determinants of influenza and pneumonia vaccination uptake following the COVID-19 pandemic. Methods: We obtained search volume data for vaccines using the Baidu search index and collected the num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Scholars have found that new vaccines usually engender more hesitancy than familiar ones [23] , [24] . After the outbreak of the COVID-19 in China, the number of influenza vaccinations increased from 2020 to 2021 [33] . Nonetheless, influenza vaccine coverage was quite low in China, with only 0.4% coverage for influenza vaccination, compared to 22.8% coverage for pneumonia vaccination (Y.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scholars have found that new vaccines usually engender more hesitancy than familiar ones [23] , [24] . After the outbreak of the COVID-19 in China, the number of influenza vaccinations increased from 2020 to 2021 [33] . Nonetheless, influenza vaccine coverage was quite low in China, with only 0.4% coverage for influenza vaccination, compared to 22.8% coverage for pneumonia vaccination (Y.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Social desirability bias might exist in both groups after intervention, especially in the intervention group. Lastly, the actual vaccination rates in both groups might be influenced by the unexpected shortage of influenza vaccines in the 2020-21 flu season because the coronavirus disease epidemic of 2019 (COVID-19) increased the demand for influenza vaccines in China [ 38 ]. The COVID-19 might also influence participants’ perceptions of knowledge and attitude towards influenza in both groups [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The research outside China is often based on the Google search engine to predict the trend of dengue fever ( 28 ) and influenza ( 29 ). The research in China [e.g., influenza ( 30 ), dengue fever ( 31 ), hand, foot, and mouth disease ( 19 ), and etc.] often uses the Baidu search index and predicts with different mathematical models.…”
Section: Discussionmentioning
confidence: 99%